Production Of Liquid Composter Using A Household Scale Biogas Reactor In The Perspective Of Toxicological Studies On Public Health - Darmayanti, Setya; Yuniarty, Tuty; Kushayati, Nuris; Sari, Mulia Safrida; Kusbandiyah, Jiarti (Jurnal Kesehatan Manarang, 2023)
Organic waste in the Health Polytechnic Of Kendari has been transported by garbage transport trucks to the Puuwatu TPAS or destroyed by burning. Burning garbage will hurt air quality. This study aims to determine the adequate time needed to produce quality liquid compost from organic waste at the Health Polytechnic Of Kendari and examine the toxicological effects of waste on human health. The results showed that the effective time for producing liquid compost was 36 days with a volume of 2500 mL, and the fastest liquid compost production was 7 days with a volume of 1200 mL. The ideal ratio of C/N composting is 30 : 1. There was a temperature fluctuation within 109 days. The mesophilic phase at the beginning of this study lasted 22 days with a temperature range of 34.5 – 34.9 oC. The second phase is the thermophilic phase, characterized by an increase in temperature, namely up to 40-54.9 oC, which lasts for 36 days. And the maturation stage in this study lasted for 51 days with a temperature range of 44.4 – 32.2 oC. The pH of liquid compost from organic waste has increased, ranging from 2.3 – 4.2. on day 7, the compost turned light brown; from day 44 to day 109, it turned dark brown. Liquid compost production from day 7 to day 85 has a distinctive odour, while liquid compost from day 95 to day 109 has a slight odour. The toxicological effects of organic waste include polluting the environment and disrupting human health, namely respiratory problems, heart problems, cancer, risk of death or premature death.